Effect of sildenafil on maternal hemodynamics in pregnancies complicated by severe early-onset fetal growth restriction: planned subgroup analysis from a multicenter randomized placebo-controlled double-blind trial - Khalil, A; Sharp, A; Cornforth, C; Jackson, R; Mousa, H; Stock, S; Harrold, J; Turner, MA; Kenny, LC; Baker, PN; Johnstone, ED; von Dadelszen, P; et al. (Wiley, 2020)
Objectives: Fetal growth restriction (FGR) is associated with maternal cardiovascular changes. Sildenafil, a phosphodiesterase type‐5 inhibitor, potentiates the actions of nitric oxide, and it has been suggested that it alters maternal hemodynamics, potentially improving placental perfusion. Recently, the Dutch STRIDER trial was stopped prematurely owing to excess neonatal mortality secondary to pulmonary hypertension. The main aim of this study was to investigate the effect of sildenafil on maternal hemodynamics in pregnancies with severe early‐onset FGR.